2010
DOI: 10.1097/prs.0b013e3181e5f7ff
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant Infections: Is Cefazolin Enough?

Abstract: Because of the high incidence of methicillin-resistant S. aureus infections in breast implant recipients, we believe that choosing an antibiotic with anti-methicillin-resistant S. aureus activity is justified for empiric treatment of breast implant infections, until culture and sensitivity data, if obtained, become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 16 publications
1
56
0
4
Order By: Relevance
“…Approximately 1 to 2.5% of breast prostheses develop infection (654)(655)(656)(657). Estimates for the proportion of these infections due to S. aureus range from 0 to 75% (655,658,659). For example, in a multicenter retrospective cohort of 106 patients with confirmed or suspected breast prosthesis infection, Feldman et al found that 68% of the 31 culture-positive breast implants grew S. aureus, 37% of which grew MRSA (658).…”
Section: Infections Involving Other Prosthetic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1 to 2.5% of breast prostheses develop infection (654)(655)(656)(657). Estimates for the proportion of these infections due to S. aureus range from 0 to 75% (655,658,659). For example, in a multicenter retrospective cohort of 106 patients with confirmed or suspected breast prosthesis infection, Feldman et al found that 68% of the 31 culture-positive breast implants grew S. aureus, 37% of which grew MRSA (658).…”
Section: Infections Involving Other Prosthetic Devicesmentioning
confidence: 99%
“…Estimates for the proportion of these infections due to S. aureus range from 0 to 75% (655,658,659). For example, in a multicenter retrospective cohort of 106 patients with confirmed or suspected breast prosthesis infection, Feldman et al found that 68% of the 31 culture-positive breast implants grew S. aureus, 37% of which grew MRSA (658). In contrast, none of the 65 culture-confirmed silicone breast infections reported by Ahn et al grew S. aureus (659).…”
Section: Infections Involving Other Prosthetic Devicesmentioning
confidence: 99%
“…The endogenous breast flora can reach deeper tissues through breast ducts or during surgery. According to different studies [11,12], the microorganism most frequently observed is coagulase-negative staphylococci but in a recent single retrospective review [28], 67% of implant infections were due to S. aureus, with methicillin resistance in 68% of these cases. In the same study, Gram-negative bacteria were reported in only 6% of infections.…”
Section: Acute Infectionsmentioning
confidence: 99%
“…The onset time of infections is different for saline implants and silicone implants: saline implant infections occur within 8 weeks (on average 4 weeks), while silicone implant infections occur within 26 weeks (on average 13 weeks) [27]. The earlier onset of saline implant infections may be linked to contamination during implant filling [28]. After augmentation mammaplasty, 0.8% of patients are affected by late infections.…”
Section: Late Infectionsmentioning
confidence: 99%
See 1 more Smart Citation